Analisis Pengaruh Penambahan Penyulang Dan Pemisahan Beban Terhadap Susut Daya Menggunakan Metode Simple Branch Exchange (Studi Kasus PT PLN ULP Lima Puluh, Sumatera Utara) - Priyadi, Irnanda; Haidi, Junas; Sihotang, Candra (UNIB Press, 2021)
AbstractDuring the distribution process there will be a loss of some of the energy that is channeled. This phenomenon is known as losses. This is caused by technical and non-technical factors. In the State Electricity Service (PLN) system, distribution losses or energy losses is calculated by measuring the difference between kWh produced and kWh sell. This kWh difference is the electrical energy lost during the starting process from the generation or secondary side of the Substation to customers’ APP. Cumulatively, the amount of kWh at all base sources is 73,769.524 kWh while the distribution loss that occurs in JTM is 5,835.008 or 7.91%. One way to overcome and minimize distribution losses in the 20 kV Procurement Service Unit (ULP) of Lima Puluh distribution system is to analyze the distribution network system, add new feeders and break the load on the electrical system. The simple branch exchange method is used to separate the network load, which is done by adding a switch by turning the on or off channel and searching for the configuration that produces the smallest power loss and calculating the power loss based on the network load. Based on the simulation results using the ETAP 12.6 software, the results of the energy loss of Procurement Service Unit (ULP) of Lima Puluh is 5,864,112 kWh then decreased after load separation of 4,341,348 kWh. The value of power loss before load separation is 1,955 kW and a decrease in power loss after load separation is 1,484.5 kW. The investment cost incurred for the construction of a new feeder is RP. 22,000,000,000,- with a payback of 9.9 years. Keywords: Feeder, Power Loss, Energy Loss, ETAP 12.6.